Influence of Magnetic Field on Atrazine Adsorption and Degradation by Ferroxite and Hematite - Marcos Antônio Sousa; Mateus Aquino Gonçalves; Thais Aparecida Sales; Jessica Boreli dos Reis Lino; Stéfany Gonçalves de Moura; Joaquim Paulo da Silva; Teodorico Castro Ramalho (Magnetism, 2025)
This study approaches the characterization of Ferroxite and Hematite and the test of their magnetic properties on the degradation and adsorption of Atrazine, an herbicide of the triazine class. This herbicide was compared with a sample of Ferroxite in the absence of a magnetic field and with Hematite, a non-magnetic material which should not be attracted by the magnet. In the sample, the Atrazine determination was carried out by Fenton analysis. Preliminary results were satisfactory, gathering a reduction rate up to 85% for Ferroxite in the presence of a magnetic field and 53% for Hematite. The Fenton reaction, however, showed an 87% reduction rate for Ferroxite in the presence of a magnetic field, and 56% for Hematite. These findings have shown that there is a relation between the magnetic field intensity and the adsorption capacity for these materials.